2022
DOI: 10.1097/md.0000000000029209
|View full text |Cite
|
Sign up to set email alerts
|

Validation of coronavirus-2019 phobia scale using preschool practitioners in urban and rural communities in Nigeria

Abstract: Coronavirus-2019 (COVID-19) emerged in December 2019, causing significant changes in people's social lives and other human activities. The outbreak halted educational activities throughout the world. The Nigerian experience was unique in that most people were skeptical about the pandemic's existence. This practice contributed to the Nigerian people's fear of the COVID-19 outbreak. However, in Nigeria, there has never been a validated or established Covid-19 phobia scale, necessitating this study. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…These outcomes were comparable to the initial C19P-S. This study, therefore, demonstrated that COVID-19 can cause phobia in the population as psychological, psychosomatic, economic, and social [9,13,[40][41][42][43][44][45].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…These outcomes were comparable to the initial C19P-S. This study, therefore, demonstrated that COVID-19 can cause phobia in the population as psychological, psychosomatic, economic, and social [9,13,[40][41][42][43][44][45].…”
Section: Discussionsupporting
confidence: 65%
“…The results of this study showed that the items in the final model of the C19P-S had convergent validity [ 44 , 45 ]. According to Hair et al, convergent validity exists when construct items are closely related and have high variance [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations